2017
DOI: 10.1016/j.jphys.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Early rehabilitation after lumbar disc surgery is not effective or cost-effective compared to no referral: a randomised trial and economic evaluation

Abstract: Netherlands Trial Register NTR3156. [Oosterhuis T, Ostelo RW, van Dongen JM, Peul WC, de Boer MR, Bosmans JE, Vleggeert-Lankamp CL, Arts MP, van Tulder MW (2017) Early rehabilitation after lumbar disc surgery is not effective or cost-effective compared to no referral: a randomised trial and economic evaluation. Journal of Physiotherapy 63: 144-153].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 36 publications
4
76
2
3
Order By: Relevance
“…In the UK, where patients live geographically dictates whether they receive rehabilitation, and if they do, the content and number of sessions of rehabilitation is inconsistent [8]. A recent RCT found no benefit (clinical effectiveness or cost-effectiveness) of early referral for physiotherapy following surgery compared to no referral [9]. Postoperative rehabilitation could possibly be harmful for patients if outcomes from the clinical course are better than outcomes of rehabilitation interventions.…”
Section: Rationalementioning
confidence: 99%
“…In the UK, where patients live geographically dictates whether they receive rehabilitation, and if they do, the content and number of sessions of rehabilitation is inconsistent [8]. A recent RCT found no benefit (clinical effectiveness or cost-effectiveness) of early referral for physiotherapy following surgery compared to no referral [9]. Postoperative rehabilitation could possibly be harmful for patients if outcomes from the clinical course are better than outcomes of rehabilitation interventions.…”
Section: Rationalementioning
confidence: 99%
“…Early referral to physiotherapy has the potential to reinforce necessary postoperative movement precautions while working on patients’ functional recovery, including mobility, transfers, sitting and lifting exercises. The results of a recent trial, however, challenge these conclusions 8. Oosterhuis et al revealed that early rehabilitation after lumbar disc surgery had no significant effect on clinical outcomes or societal costs compared with no referral 8…”
Section: Discussionmentioning
confidence: 99%
“…Supervised exercise therapy can be a high-value alternative to surgery and harmful pharmacological treatments, but optimizing value remains vital. There are many situations where intensive supervision for recreational athletes or the general population adds no benefit to a home-based program involving minimal supervision (eg, following an ACL reconstruction, [69][70][71] following lumbar disc surgery, 72,73 post-immobilization of an ankle 74 or distal radius fracture, 75 management of rotator cuff tendinopathy 76 ). For example, a randomized controlled trial of 145 recreational athletes following an ACL reconstruction found no difference in quality of life, range of motion, laxity, and quadriceps or hamstring strength at any time (up to 4 years) between athletes that received 17 sessions of supervised exercise compared to 4 sessions (eg, limb symmetry index scores for peak quadriceps torque at 60 degrees/s were similar between groups: mean difference (MD) 7.0%, 95% CI: −4.6 to 18.7, P = .23, n = 60).…”
Section: Exercise Therapymentioning
confidence: 99%
“…72 In fact, a more recent randomized controlled trial (n = 169) found that exercise therapy commencing within 1 week of discharge was not superior to no treatment for improving pain and disability at any time point following lumbar disc surgery (up to 6 months), and instead, led to higher medical costs. 73 A randomized controlled trial of 33 patients' post-immobilization of a distal radius fracture found that a 6-week structured exercise program plus three sessions of structured advice with a physiotherapist was not superior to advice alone for improving upper limb activity, range of motion, strength, or pain. 75 For patients with rotator cuff tendinopathy, a randomized controlled trial (n = 86) found that usual physiotherapy was not superior to a self-management program involving a single exercise for improving pain and disability, function, and quality of life.…”
Section: Exercise Therapymentioning
confidence: 99%